(3HMhK GdYedjGJ aj GdeMGSHIs (3eONd eYGUQ HESJNOGe GdMGSH GdCdjs - (3Ydj MSjf(B, (3CMeO MSjfs; (3GdShGaQjs ((3GdEScfOQjIs (3GdOGQ GdLGeYjIs, 2002)
(3jJfGhd gPG GdcJGH aj WjGJg JMdjd GdbQGQ CSGdjH GdHQeLI GdNWjI hGdYOOjI hGdCgOGa heLehYI ef feGPL GdJMdjds
Keywords: (3GdMGSH GdBdjs; (3GdeMGSHIs